Bioactive MXene hydrogel promotes structural and functional regeneration of skeletal muscle through improving autophagy and muscle innervation - Li Zhou; Haixia Zhuang; Xinyu Ye; Wei Yuan; Kai Wang; Donghan Hu; Xiangya Luo; Qiuyu Zhang (Smart Materials in Medicine)
Complete skeletal muscle regeneration after traumatic injuries remains a challenge due to impaired regenerative capability and dysregulated microenvironments. Autophagy plays a crucial role in the muscle regeneration process by regulating myogenic and non-myogenic cells. Herein, we report a bioactive MXene hydrogel (FPGM) capable of upregulating autophagy and increasing muscle innervation to restore skeletal muscle structure and function. FPGM possessed excellent electrical conductivity, tissue adhesive ability and antioxidation, which could eliminate excess reactive oxygen species to reduce oxidative stress and decrease the secretion of pro-inflammatory cytokine. FPGM upregulated the autophagy level of myoblasts and promoted the migration and tube formation of endothelial cells as well as myogenic differentiation with negligible toxicity. FPGM accelerated muscle fiber formation and skeletal muscle regeneration by improving autophagy, which could regulate microenvironment through raising M2 macrophages to alleviate excessive inflammation, facilitating angiogenesis and decreasing fibrous scar tissue formation in vivo. Importantly, FPGM could efficiently restore muscle function by improving muscle innervation, tibialis anterior compound muscle action potential amplitude and neuromuscular conduction. This work demonstrates that bioactive MXene hydrogel should be a promising candidate for complete skeletal muscle regeneration.